Levator ani avulsion: a Systematic evidence review (LASER) - Rusavy, Z; Paymova, L; Kozerovsky, M; Veverkova, A; Kalis, V; Kamel, R A; Ismail, K M (BJOG, 2022)
BACKGROUND: There is variation in the reported incidence rates of levator avulsion (LA) and paucity of research into its risk factors. OBJECTIVE: To explore the incidence rate of LA by mode of birth, imaging modality, timing of diagnosis and laterality of avulsion. SEARCH STRATEGY: We searched MEDLINE, EMBASE, CINAHL, AMED and MIDIRS with no language restriction from inception to April 2019. STUDY ELIGIBILITY CRITERIA: A study was included if LA was assessed by an imaging modality after the first vaginal birth or caesarean section. Case series and reports were not included. DATA COLLECTION AND ANALYSIS: RevMan v5.3 was used for the meta-analyses and SW SAS and STATISTICA packages were used for type and timing of imaging analyses. RESULTS: We included 37 primary non-randomised studies from 17 countries and involving 5594 women. Incidence rates of LA were 1, 15, 21, 38.5 and 52% following caesarean, spontaneous, vacuum, spatula and forceps births, respectively, with no differences by imaging modality. Odds ratio of LA following spontaneous birth versus caesarean section was 10.69. The odds ratios for LA following vacuum and forceps compared with spontaneous birth were 1.66 and 6.32, respectively. LA was more likely to occur unilaterally than bilaterally following spontaneous (P < 0.0001) and vacuum-assisted (P = 0.0103) births but not forceps. Incidence was higher if assessment was performed in the first 4 weeks postpartum. CONCLUSIONS: LA incidence rates following caesarean, spontaneous, vacuum and forceps deliveries were 1, 15, 21 and 52%, respectively. Ultrasound and magnetic resonance imaging were comparable tools for LA diagnosis. TWEETABLE ABSTRACT: Levator avulsion incidence rates after caesarean, spontaneous, vacuum and forceps deliveries were 1, 15, 21 and 52%, respectively.
Keywords: ventouse; ultrasound; caesarean; Pregnancy; Humans; vacuum; vakuová extrakce porodnická; Female; pelvic floor; onemocnění dna pánevního; Pelvic Floor Disorders; operative; lidé; perineum; magnetic resonance imaging; prolapse; Assisted birth; transperineal; ženské pohlaví; parturition; Cesarean Section; forceps; incidence; Incidence; těhotenství; hiatus; Vacuum Extraction, Obstetrical; labour; birth; císařský řez